An application of star polynomials to discrete random allocation problems - Farrell, Edward J.; Gargano, Michael L.; Quintas L.V. (Utilitas Mathematica, 2005)
The star polynomial of a graph can be used to investigate certain models associated with random space filling problems -a type of allocation problem. In particular, various discrete forms of Renyi's Random Parking Problem (see Grimaldi [3], Renyi [4] and Rosen[5]) can be modeled by star covers of chains. There are also similar finite resource allocation problems in Computer Science which can be investigated, by means of star polynomials of graphs.